2009
DOI: 10.1590/s0102-33062009000300016
|View full text |Cite
|
Sign up to set email alerts
|

A new case of late-acting self-incompatibility in Capparis L. (Brassicaceae): C. jacobinae Moric. ex Eichler, an endemic andromonoecious species of the Caatinga, Pernambuco State, Brazil

Abstract: . We studied the reproductive system of Capparis jacobinae Moric ex Eichler (Brassicaceae), based on controlled hand-pollination and observation of pollen tube growth made in a fluorescence microscope. Of 105 self-pollinated flowers only one produced fruits (success = 0.95%), all the other flowers abscised at the same time, between the eighth and tenth day after anthesis. Nevertheless, self-and cross-pollinated pollen tubes reached the micropyle. The rate of penetrated ovules in selfpollinated flowers was lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 20 publications
0
5
0
4
Order By: Relevance
“…This latter observation is curious because in other species a normal embryo-sac with synergid cells seems to be necessary for pollen tube penetration to occur (Ray et al, 1997;Higashiyama et al, 1998). Sage et al (2006) reported a somewhat similar situation in Ipomopsis aggregata, another species with LSI (Waser & Price, (Beardsell et al, 1993) Melaleuca alternifolia (Baskarowati et al, 2010) Vochysiaceae Callisthene major (Oliveira, 1998) Qualea grandiflora; Q. multiflorum (Oliveira, 1998); Q. cordata (P. E. Gibbs & S. Godoy-Aveiro, unpublished) SAPINDALES Anacardiaceae Anacardium occidentale (Wunnachit et al, 1992) Sapindaceae (Xanthoceraceae) Xanthoceras sorbifolium (Zhou & Liu, 2012) MALVALES Malvaceae Sterculioideae Cola nitida (Jacob, 1970) Sterculia chicha (Taroda & Gibbs, 1982) Theobroma cacao; T. grandiflorum; T. speciosum (Cope, 1962;Ramos et al, 2005;De Souza & Venturieri, 2010) Dombeyoideae Dombeya acutangula (Gigord et al, 1998) Bombacoideae Adansonia gibbosa (Baum, 1995) Bombacopsis quinata (Sandiford, 1998) Ceiba chodatii, C. speciosa; C. pentandra (Gibbs & Bianchi, 1993;Gribel et al, 1999) Eriotheca gracilipes; E. candolleana (Oliveira et al, 1992;Gomes da Silva, 1997) Pseudobombax munguba (Gribel & Gibbs, 2002) Grewioideae Luehea seemanii (Bawa et al, 1985) Bixaceae Cochlospermum vitifolium (Bawa & Webb, 1984) BRASSICALES Capparaceae Capparis jacobinae; C. pittieri; C. retusa (Bawa et al, 1985;Bianchi & Gibbs, 2000;Primo & Machado, 2009) Asterids ERICALES Theaceae Camellia sinensis (Chen et al, 2012) Polemoniaceae Ipomopsis aggregata; I. tenuifolia (Waser & Price, 1991;La Doux & Friar, 2006;…”
Section: Antagonistic Reactions Between the Pistil And Pollen Tubes Imentioning
confidence: 99%
“…This latter observation is curious because in other species a normal embryo-sac with synergid cells seems to be necessary for pollen tube penetration to occur (Ray et al, 1997;Higashiyama et al, 1998). Sage et al (2006) reported a somewhat similar situation in Ipomopsis aggregata, another species with LSI (Waser & Price, (Beardsell et al, 1993) Melaleuca alternifolia (Baskarowati et al, 2010) Vochysiaceae Callisthene major (Oliveira, 1998) Qualea grandiflora; Q. multiflorum (Oliveira, 1998); Q. cordata (P. E. Gibbs & S. Godoy-Aveiro, unpublished) SAPINDALES Anacardiaceae Anacardium occidentale (Wunnachit et al, 1992) Sapindaceae (Xanthoceraceae) Xanthoceras sorbifolium (Zhou & Liu, 2012) MALVALES Malvaceae Sterculioideae Cola nitida (Jacob, 1970) Sterculia chicha (Taroda & Gibbs, 1982) Theobroma cacao; T. grandiflorum; T. speciosum (Cope, 1962;Ramos et al, 2005;De Souza & Venturieri, 2010) Dombeyoideae Dombeya acutangula (Gigord et al, 1998) Bombacoideae Adansonia gibbosa (Baum, 1995) Bombacopsis quinata (Sandiford, 1998) Ceiba chodatii, C. speciosa; C. pentandra (Gibbs & Bianchi, 1993;Gribel et al, 1999) Eriotheca gracilipes; E. candolleana (Oliveira et al, 1992;Gomes da Silva, 1997) Pseudobombax munguba (Gribel & Gibbs, 2002) Grewioideae Luehea seemanii (Bawa et al, 1985) Bixaceae Cochlospermum vitifolium (Bawa & Webb, 1984) BRASSICALES Capparaceae Capparis jacobinae; C. pittieri; C. retusa (Bawa et al, 1985;Bianchi & Gibbs, 2000;Primo & Machado, 2009) Asterids ERICALES Theaceae Camellia sinensis (Chen et al, 2012) Polemoniaceae Ipomopsis aggregata; I. tenuifolia (Waser & Price, 1991;La Doux & Friar, 2006;…”
Section: Antagonistic Reactions Between the Pistil And Pollen Tubes Imentioning
confidence: 99%
“…LSI has been reported for many families (Seavey and Bawa,1986), but S. obtusifolium, from this study, represents the first report of this kind of mechanism for Sapotaceae. Other Caatinga species of many families such as Caesalpinia calycina (Leguminosae) (Lewis and Gibbs, 1999) and Capparis jacobinae (Brassicaceae) (Primo and Machado, 2009), as well as for genera examined in other ecosystems that have representatives in these drylands, such as Tabebuia (Bignoniaceae) (Bittencourt Jr. and Semir, 2005) and Pseudobombax (Bombacaceae) (Gribel and Gibbs, 2002) were also registered as LSI. Considering that this mechanism may occur in other species of the same family or genus (see Seavey and Bawa, 1986;Bittencourt Jr. and Semir, 2005;Primo and Machado, 2009), it is likely that the number of species in the Caatinga with this type of self-incompatibility is even greater.…”
Section: Breeding Systemsmentioning
confidence: 99%
“…Esse sistema de incompatibilidade no qual flores autofecundadas são abortadas apenas após os óvulos serem atingidos pelos tubos polínicos, denominado sistema de autoincompatibilidade de ação tardia (LSI) (Seavey & Bawa 1986), ocorre em várias espécies de outras famílias, como Apocynum cannabinum L., Apocynaceae (Lipow & Wyatt 1999); Casearia grandiflora Cambess., Flacourtiaceae (Machado & Oliveira 2000); Capparis retusa Griseb., Capparaceae (Bianchi & Gibbs 2000), espécies de Kielmeyera, Clusiaceae (Barros 2002) e de Eucalyptus, Myrtaceae (Pound et al 2003); Capparis jacobinae Moric. ex Eichler, Brassicaceae (Primo & Machado 2009).…”
Section: Sistema Reprodutivounclassified
“…Foram encontradas duas características reprodutivas em I. edulis e I. stipularis, que se enquadram no sistema de autoincompatibilidade de ação tardia: primeiramente, as espécies analisadas no presente estudo apresentam padrão de abscisão de flores autopolinizadas uniforme e precoce, embora os tubos polínicos provenientes desse tratamento alcancem os sacos embrionários, no qual não existe no sistema esporofítico ou gametofítico; segundo, o tempo de penetração a b c d dos tubos polínicos nos óvulos são similares entre as autopolinizações e as polinizações cruzadas, o que é semelhante ao encontrado por Bianchi & Gibbs (2000) em Capparis retusa; por Primo & Machado (2009) Taxa de frutificação e abscisão de flores e frutos em condições naturais…”
Section: Sistema Reprodutivounclassified